2012
DOI: 10.1593/tlo.11325
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles in Stage II Colon Cancer According to APC Gene Status

Abstract: Colorectal cancer is one of the most common cancers in the world. Histoclinical staging is efficient, but combination with molecular markers may improve the classification of stage II cancers. Several tumor-suppressor genes have been associated with colorectal cancer, and the most frequent allelic losses have been extensively studied for their prognosis effect, but the results remain controversial. In a previous study, we found a possible influence of the chromosome 5 status in the development of liver metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…As has been reported by others in CRC stage II [36,42], BRAF mutation here was not associated with RFS or with cancer-specific survival. However, BRAF is generally considered an independent predictor of a poor prognosis, and growing evidence suggests that this is particularly true for MSI stable tumors [12,14,35,36,39,41].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As has been reported by others in CRC stage II [36,42], BRAF mutation here was not associated with RFS or with cancer-specific survival. However, BRAF is generally considered an independent predictor of a poor prognosis, and growing evidence suggests that this is particularly true for MSI stable tumors [12,14,35,36,39,41].…”
Section: Discussionsupporting
confidence: 84%
“…Central gene mutations (KRAS, NRAS, BRAF, APC, and CTNNB1) in these pathways are almost mutually exclusive [33,43]. Separate and combined analysis of these genes has been associated with RFS in MSI stable stage III patients, but not in MSI stable stage II patients [38,42]. Similar observations were done here in stage II, although MSI status was unknown in our study population.…”
Section: Discussionsupporting
confidence: 70%
“…A transcriptional signature was developed and evaluated for its ability to stratify patient outcome as we have done before (29). We analyzed 4 bladder cancer (2326) and 5 colorectal cancer (3034) patient datasets with common microarray technology because of the relevance of CD24 in both bladder cancer (11) and colon cancer (15,35). We analyzed additional patient datasets, based on large sample sizes and common microarray platforms, for 3 other cancer types (3638) for which we’ve confirmed the existence of nucCD24 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Poor prognosis of APC- wt/MSS proximal tumours was validated in an independent patient cohort ( Marisa et al , 2013 ) using a predictor of APC -wt status from microarray expression data. Most previous studies evaluating APC mutation status have not identified a relationship with prognosis ( Dix et al , 1994 ; Conlin et al , 2005 ; Hsieh et al , 2005 ; Chen et al , 2009 ; Birnbaum et al , 2012 ). However, these studies did not consider CRC groups by tumour location and MSI status, likely precluded by their smaller sample sizes ( n =100–218), and only performed mutation screening for limited regions of the APC gene.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in APC have a principal role in CRC initiation, their relation to outcome remains unclear. Most previous studies have not found an association between the presence of APC mutation and prognosis, but these analysed small patient cohorts, only screened limited regions of the APC gene, and did not account for prognostically important features such MSI, CIN, BRAF mutation and tumour location ( Dix et al , 1994 ; Løvig et al , 2002 ; Conlin et al , 2005 ; Hsieh et al , 2005 ; Meguid et al , 2008 ; Chen et al , 2009 ; Wong, 2010 ; Birnbaum et al , 2012 )…”
mentioning
confidence: 99%